Structural cohesion in Europe: Stylized facts - Frank Bickenbach; Eckhardt Bode; Christiane Krieger-Boden (Kiel Institute for the World Economy (IfW), 2010)
This paper establishes eight stylized facts on the evolution of the localization of economic activity across industries and regions in the EU-15 since 1980. Localization, which nests concentration and specialization, is measured by a Theil index. The stylized facts reveal a broad aggregate trend towards structural convergence in the EU-15. The by far most important drivers of this convergence have been the sectoral structural change from highly concentrated agriculture and manufacturing industries towards dispersed services, and a continuing dispersion of services. The manufacturing sector, by contrast, worked against this structural convergence as it has become spatially more concentrated. The stylized facts also reveal that virtually all countries and most of their regions participated in this structural convergence. The speed of aggregate structural cohesion slowed down considerably in the early 1990s, however.
Keywords: C43; F15; R12; 330; Theil index; localization; specialization; concentration; European Union; cohesion; Lokalisationseffekt; Regionale Arbeitsteilung; Regionale Konzentration; Entwicklungskonvergenz; Strukturwandel; EU-Staaten